Pengembangan Baja Paduan Tahan Peluru Melalui Proses Hot-Forging Terhadap Morfologi Dan Sifat Mekanik - Putra, Ilham Nugrahatama (Universitas Nusantara PGRI Kediri, 2022)
Laterite steel is steel that has a nickel content of up to 2%. The nickel content can produce steel with superior properties such as: high strength, corrosion resistance, and good weldability properties. With the superior nature of laterite steel is needed in the main tool of the indonesian national tantara weapon system. To find out the performance of damage to bulletproof materials, then conducted research on this laterite steel as a tough armour material by conducting research in the form of mechanical properties testing (Hardness, and Impact) and microstructures (Metalography). Samples are prepared in accordance with ASTM standardization. Based on the results of the hardness test, the average values of F and T samples were 663.9 HVN and 170.7 HVN. Material F qualifies as a ballistic resistant material (armour) because the hardness obtained in accordance with the classification and can withstand bullet penetration well. Then the impact test obtained the average value of the F and T samples is 9 joules and 148 joules. For F samples, the type of fault is a granular fracture and a T sample of the type of fault is a tenacious fracture. As a result of metallographics, sample F has a corrected phase is upper bainite as a matrix and martensite is generally shaped like a fine needle. Then the T sample has a formed phase is dominated by ferrite with soft and tenacious properties. As well as perlite as a matrix with quite hard and strong properties.